Stabilization of heavy metals loaded sewage sludge: Reviewing conventional to state-of-the-art thermal treatments in achieving energy sustainability. (August 2021) - Liew, Chin-Seng; Kiatkittipong, Worapon; Lim, Jun-Wei; Lam, Man-Kee; Ho, Yeek-Chia; Ho, Chii-Dong; Ntwampe, Seteno K.O.; Mohamad, Mardawani; Usman, Anwar
Abstract: Sewage sludge has long been regarded as a hazardous waste by virtue of the loaded heavy metals and pathogens. Recently, more advanced technologies are introduced to make use of the nutrients from this hazardous sludge. Successful recovery of sludge's carbon content could significantly convert waste to energy and promote energy sustainability. Meanwhile, the recovery of nitrogen and trace minerals allows the production of fertilizers. This review is elucidating the performances of modern thermal treatment technologies in recovering resources from sewage sludge while reducing its environmental impacts. Exhaustive investigations show that most modern technologies are capable of recovering sludge's carbon content for energy generation. Concurrently, the technologies could as well stabilize heavy metals, destroy harmful pathogens, and reduce the volume of sludge to minimize the environmental impacts. Nevertheless, the high initial investment cost still poses a huge hurdle for many developing countries. Since the initial investment cost is inevitable, the future works should focus on improving the profit margin of thermal technologies; so that it would be more financially attractive. This can be done through process optimization, improved process design as well as the use of suitable co-substrates, additives, and catalyst as propounded in the review. Graphical abstract: Image 1 Highlights: Resources recovery from sewage sludge while stabilizing heavy metals and pathogens. Generation of sewage sludge byproducts in the form of biogas, bio-oil and biochar. Sustainable ways forward to produce green energies from sewage sludge feedstock.